2016
DOI: 10.1155/2016/8608602
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Outcome for Retreatment Pulmonary Tuberculosis Cases among Tribal People of an Eastern India District: A Prospective Cohort Study

Abstract: Objective. The study was conducted to assess the treatment outcome of different category retreatment cases with the aim of finding out the important predictors of unfavorable outcomes. Methodology. This hospital based prospective cohort study was conducted in three tuberculosis units (TUs) of west Midnapore (a district of Eastern India), covering mostly the tribal populated areas. Patients who were registered for Category II antituberculosis treatment between 1st quarter of 2013 (Jan to Mar) and 4th quarter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…Ravahatra [12] reported a rate of 35.84% of favourable outcome. Nevertheless, these rates are much lower than those reported by Saha [13] (75.2%) in India and by Agodokpessi [14] (80%) in Benin.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…Ravahatra [12] reported a rate of 35.84% of favourable outcome. Nevertheless, these rates are much lower than those reported by Saha [13] (75.2%) in India and by Agodokpessi [14] (80%) in Benin.…”
Section: Resultscontrasting
confidence: 64%
“…Regarding success by type of tuberculosis in our series, patients undergoing re-treatment after treatment after default or failure of tuberculosis treatment had more unfavourable outcomes than patients who were relapsing treatment. Saha [13] had found that the rate of unfavourable treatment outcome was more frequent on defaulter also. For Gninafon [10], the therapeutic success rate was comparable between relapses (80%) and failures (85%), but significantly lower (p < 0.01) for treatment after default (59%).…”
Section: Factors Associated With Unfavourable Treatment Outcomementioning
confidence: 99%
“…Characteristics identified as risk factors for TB based on prior evidence were: as follows inadequate ventilation (Mfinanga et al, ), approximated by “Number of windows”; crowding within the household (Waziri et al, ), approximated by “Number of people sleeping together in a single room”; knowledge of TB, judged to be “yes” if the response to the household survey question “Have you heard of [zoonotic] diseases before,” was “TB” or “yes, TB” (Katale et al, ); religion, defined by the corresponding household survey question (Saha, ); self‐reported age (Yen et al, ); exposure to human TB cases, defined by TST results in other household members; and socioeconomic status (SES) (Siroka et al, ), approximated by house structure, number of rooms in the home, cattle herd size and educational attainment of household survey respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, delayed return to care and resulting advanced disease may also explain our finding of increased mortality in those presenting after LTFU (aHR=8.27). Cohorts from India and Uganda have also shown higher mortality amongst RT-TB patients returning after LTFU [12, 14]. Attempts for early recognition of LTFU and innovated methods for rapid re-engagement in care may also be critical to lower RT-TB mortality rates.…”
Section: Discussionmentioning
confidence: 99%